Moral Attitude as an Object of Scientific Cognition - Kriaučiūnienė, Roma (Acta Paedagogica Vilnensia, 2007)
The article gives an overview of the moral attitude phenomenon in psychological and philosophical litarature. Theoretical and empirical findings in psychological literature show that the concept of attitude is the most distinctive and indispensable concept in contemporary psychology. Such enormous interest in attitude research proves the fact that an attitude is a very important integral part of a personality structure. Moreover, attitudes are said to predict, determine and even modify human behaviour. Psychologists present different models of attitude structure. The first one-component attitude model is defined as the affect for or against a psychological object and is considered to express an opinion or an evaluation of an attitude object. According to a dual aspect model an attitude is regarded to have affective and cognitive aspects which arc not to he conceived as separate components hut as aspects or properties of the same behaviour. A third view is a three - component attitude model consisting of cognitive, affective and behavioural components. This three-fold division stresses thought, feeling and action as basic to human behaviour. However, this model presents a problem by prejudging a link between attitude and behaviour, whereas dual aspect attitude model is considered to be an integral part of a human behaviour. Therefore, this attitude structure provides the greatest insight into human behaviour. Valuable insights of moral attitudes are found in existential philosophy, which focuses on the analysis of a free choice made by an individual. One’s freedom to choose as well as a moral judgement are closely related with one’s responsibility and respect for others. From the point of view of non-cognitivism a person’s moral attitude and consequently a moral judgement have a motivating power on the individual, whereas cognitivists claim that beliefs themselves motivate a person. Moral judgements arc claimed to be evaluative processes by cognitivists as well as by non-cognitivists. The latter consider attitudes to be evaluative in nature and equivalent to evaluation itself. They also agree that a moral judgement about an object or a phenomenon can be made only if one has an attitude towards them. Philosophers as well as psychologists agree that moral attitudes manifest themselves by moral evaluative judgements.